Characterization of a 3xTg‐AD mouse model of Alzheimer's disease with the senescence accelerated mouse prone 8 (SAMP8) background. Issue 4 (1st February 2018) - Virgili, Jessica; Lebbadi, Meryem; Tremblay, Cyntia; St‐Amour, Isabelle; Pierrisnard, Caroline; Faucher‐Genest, Audrey; Emond, Vincent; Julien, Carl; Calon, Frédéric
Abstract: No model fully recapitulates the neuropathology of Alzheimer's disease (AD). Although the triple‐transgenic mouse model of AD (3xTg‐AD) expresses Aβ plaques and tau‐laden neurofibrillary tangles, as well as synaptic and behavioral deficits, it does not display frank neuronal loss. Because old age is the most important risk factor in AD, senescence‐related interactions might be lacking to truly establish an AD‐like environment. To investigate this hypothesis, we bred the 3xTg‐AD mouse with the senescence‐accelerated mouse prone 8 (SAMP8), a model of accelerated aging. We generated four groups of heterozygous mice with either the SAMP8 or SAMR1 (senescence‐resistant‐1) genotype, along with either the 3xTg‐AD or non‐transgenic (NonTg) genotype. Despite no differences among groups in total latency to escape the Barnes maze, a greater number of errors were noticed before entering the target hole in 19‐month‐old P8/3xTg‐AD mice at day 5, compared to other groups. Postmortem analyses revealed increased cortical levels of phospho‐tau (Thr231) in female P8/3xTg‐AD mice (+277% vs. R1/3xTg‐AD mice), without other tau‐related changes. Female P8/3xTg‐AD mice exhibited higher cortical soluble Aβ40 and Aβ42 concentrations (Aβ40, +85%; Aβ42, +35% vs. R1/3xTg‐AD), whereas insoluble forms remained unchanged. Higher Aβ42 load coincided with increased astroglial activation in female P8/3xTg‐AD mice, as measured with glial fibrillary acidic protein (GFAP) (+57% vs. R1/3xTg‐AD mice). To probe neuronal degeneration, concentrations of neuronal nuclei (NeuN) were measured, but no differences were detected between groups. Altogether, the SAMP8 genotype had deleterious effects on spatial memory and exerted female‐specific aggravation of AD neuropathology without overt neurodegeneration in 3xTg‐AD mice. Abstract : Heterozygous female 3xTg‐AD mice with senescence‐accelerated prone 8 (SAMP8) background displayed a more severe AD‐like neuropathology compared to senescence‐resistant‐1 (SAMR1) controls.